ChemInform Abstract: Expedient Synthesis of Tetrafluorophenoxthiines and Derivatives by Copper(I)‐Catalyzed Cross‐Coupling Reaction. Issue 16 (22nd April 2014) - Yu, Chuanming; Hu, Gaobo; Zhang, Cuiling; Wu, Ran; Ye, Haiwei; Yang, Guanghui; Shi, Xiangjun
Abstract Pentafluorobenzene and aryl mercaptanes or the corresponding diaryl disulfides undergo an interesting oxidative coupling reaction to give tetrafluorophenoxthiines in moderate yields.